Evaluation of specialist outreach health care services - Dharmagunawardene, P.V.D.S (My University, 2007)
Health care is a fundamental need and right of any civilized community and health care systems have been developed from time immemorial to provide this essential need. Basic goals of a health care delivery system are; provision of health care, fair financing and responsiveness. In provision of health care, it is essential to consider equity and access to health care. Cost of health care is gaining importance in a rapidly economizing world and patient satisfaction has become an essential consideration in service provision in recent years. To Evaluate Specialist Outreach Clinics conducted in selected districts with reference to improvement of Geographical and Temporal accessibility, Service Outcome, Patient satisfaction, Cost to the patient and service provider, contribution to reduce overcrowding in secondary and tertiary level of health care and possible contribution to increasing utilization of inpatient services at primary care level. Geographical and convenience of access to specialist services was significantly improved through outreach clinics. Waiting time reduction for Wariyapola and Mahawa outreach was significantly less at 99 percent level. For Piliyandala Outreach it was significant at 95 percent Level. Cost for the patients was significantly reduced due to outreach specialist clinics. In terms of cost efficiency and service outcome, Wariyapola Rheumatology clinic was the best and in terms of patient satisfaction it was Mahawa Antenatal clinic. Patients were mostly satisfied with outreach clinics due to the improvement of geographical access and due to performance of staff. They perceive money and time savings as the most advantageous. Medical officers felt that convenience of access for patients, reduction of overcrowding and improvement of knowledge and skills of primary care officers were the main advantages. Secondary data survey revealed that, there is no improvement in bed occupancy rates in primary care institutions, where outreach clinics are held. But there was a reduction in overcrowding in Rheumatology and Antenatal clinics of Kurunegala T.H. after the commencement of outreach clinics. Patients obtain significant improvement in access to specialist services, cost reduction and satisfaction through outreach specialist clinics. Those in Kurunegala District were the more beneficial. Thus it could be inferred that outreach services to less accessible communities are beneficial